2001
DOI: 10.1029/2001gl013363
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Pacific basin‐wide adjustment and oceanic waves

Abstract: Abstract.This study examines the basin-wide adjustment process associated with E1 Nifio-Southern Oscillation (ENSO) in terms of oceanic waves using the Cane-Zebiak model. The Rossby waves induce not only the meridional mass divergence in the ocean interior but also the incoming zonal mass flux at the western boundary, which generally overcompensates the interior meridional divergence. Therefore, the Rossby waves alone cannot make a negative feedback. However, the outgoing zonal mass flux associated with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Previous theoretical (e.g., Zebiak 1989;An and Kang 2001) and observational (Meinen and McPhaden 2001) work has suggested that this western boundary layer transport and, therefore, TЈ W contribute significantly. However TЈ W could not be estimated as directly as the other terms in (2.15) because the geostrophic ocean current estimates at 156°E, generously provided by Christopher Meinen (Meinen and McPhaden 2001;Meinen 2005), were only available at 3.5°S, 0°, 3.5°, and 6.5°N.…”
Section: Comparison Of the Theory With Observationsmentioning
confidence: 96%
“…Previous theoretical (e.g., Zebiak 1989;An and Kang 2001) and observational (Meinen and McPhaden 2001) work has suggested that this western boundary layer transport and, therefore, TЈ W contribute significantly. However TЈ W could not be estimated as directly as the other terms in (2.15) because the geostrophic ocean current estimates at 156°E, generously provided by Christopher Meinen (Meinen and McPhaden 2001;Meinen 2005), were only available at 3.5°S, 0°, 3.5°, and 6.5°N.…”
Section: Comparison Of the Theory With Observationsmentioning
confidence: 96%
“…In BH89 (i.e., equation ), ⟨ h ⟩ is the reflected Kelvin wave, but we use the zonal mean thermocline depth over the equatorial band (5°S–5°N). This approximation (i.e., ⟨ h ⟩ ≈ h reflected Kelvin ) is quite reasonable because the forced Kelvin waves mainly over the eastern Pacific and the forced Rossby waves mainly over the western Pacific almost cancel each other by averaging over an equatorial band [ An and Kang , ]. As shown in Figure c, the maximum correlation is observed when ⟨ τ x ⟩ leads ⟨ h ⟩ by 12 months ( r = −0.447; α < 0.01).…”
Section: Asymmetry In a Delayed Negative Feedbackmentioning
confidence: 99%
“…The β h is basically affected by two factors: ocean stratification and wind stress pattern/intensity (i.e., its zonal and meridional shape) [e.g., An and Kang, 2001;Chen et al, 2015;Im et al, 2015;An and Kim, 2017]. The β h is basically affected by two factors: ocean stratification and wind stress pattern/intensity (i.e., its zonal and meridional shape) [e.g., An and Kang, 2001;Chen et al, 2015;Im et al, 2015;An and Kim, 2017].…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…Under a simple dynamical framework, we have β h ≈ L 2ρ o g 0 H [Hirst, 1986;An and Kang, 2001;An and Bong, 2016], where L is the ocean basin length, H is the mean thermocline depth, ρ ο is the ocean water density, and g 0 is the reduced gravity. An inverse relationship between β h and the mean thermocline depth might be due to that most wind stress momentum is trapped above the thermocline [An and Bong, 2016;An and Kim, 2017].…”
Section: Geophysical Research Lettersmentioning
confidence: 99%